Heat, rain and livestock: Impacts of climate change on Africa’s livestock herders - International Livestock Research Institute (International Livestock Research Institute, 2010)
What’s the future for Africa’s livestock herders as our climate changes, becomes less predictable, heats up? How can scientific research help remote pastoral communities? Among the poorest of the world’s poor, herders supply milk and meat not only for themselves but for large numbers of other poor people. Although their animals produce few of the greenhouse gasses harming the earth, these people will be among those most hurt by the climate changes we expect. Population growth and land degradation are already causing problems over much of the continent’s traditional rangelands. Many herders, having lost all their animals to droughts, are facing the end of their way of life. Research-based approaches for adapting to climate change, however, offer options that can help herding communities sustain at least some aspects of their pastoral livelihoods.